In Situ Loading Transition Metal Oxide Clusters on TiO2 Nanosheets As Co-catalysts for Exceptional High Photoactivity - Liu, Lichen; Ji, Zeyang; Zou, Weixin; Gu, Xianrui; Deng, Yu; Gao, Fei; Tang, Changjin; Dong, Lin (ACS catalysis, 2013)
In this work, transition metal oxide clusters (MnO x , FeO x , CoO x , NiO x , and CuO x , denoted as TM-TiO2) are in situ loaded on TiO2 nanosheets through one-pot reaction. Structural and pore structural characterizations prove that metal ions do not dope into the frameworks of TiO2 nanosheets. Through TEM and STEM, we can determine that clusters with ∼2 nm size are finely dispersed on TiO2 nanosheets. PL spectra and photoelectrochemical measurements suggest that these metal oxide clusters can serve as hole traps. Time-resolved PL spectra demonstrate that the charge-transfer process in TM-TiO2 is significantly accelerated, leading to higher charge separation efficiency. Metal oxide clusters show significant promotion effect in photocatalytic water oxidation to O2 compared to RuO2/TiO2 and IrO2/TiO2 nanosheets (denoted as Ru-TiO2(IM) and Ir-TiO2(IM)) prepared through conventional impregnation method. We also prepared RuO2/TiO2 and Ir/TiO2 nanosheets (denoted as Ru-TiO2(HT) and Ir-TiO2(HT)) through the in situ loading method. Ru-TiO2(HT) and Ir-TiO2(HT) show O2 evolution rates much better than those of Ru-TiO2(IM) and Ir-TiO2(IM) due to the smaller sizes of RuO2 and IrO2. However, Mn-TiO2 and Co-TiO2 still display better photoactivities compared to those of Ru-TiO2(HT) and Ir-TiO2(HT). These results indicate that transition metal oxides with small sizes can also work as co-catalysts in photocatalysis to substitute noble metal oxides.